“I Am Very, Very Proud of Myself”: Improving Youth Activity Levels Using Self-Determination Theory in Program Development - Springer, Judy B. (Frontiers in Public Health, 2013)
Many adolescents are not meeting recommended levels for physical activity. Increasing physical activity among urban African American youth is both a challenge and a public health priority. Most research in community-based interventions has taken a didactic approach, focusing on skill and knowledge development alone, with inconclusive results. This ten-week progressive activity intervention with adolescents in an urban faith community introduced a self-determination theory (SDT) approach with the aim of promoting the adoption of self-management skills necessary for sustaining activity. Components of SDT included relatedness, competence, and autonomy. Together with didactics, aligning activities with participant interests, and using existing social structures for health message delivery, the approach led to high satisfaction ratings for the three components of SDT along with improved skills, knowledge, and outcomes in cardiovascular fitness. Understanding and utilizing approaches that enhance enjoyment, personal choice, confidence, and social affiliation may lead to more lasting healthy activity behaviors and attitudes than didactic approaches alone in this and other adolescent populations. The SDT is reviewed in the context of this youth intervention.